ARRANGEMENTS REGARDING PROPERTY AS A LEGAL CONSEQUENCE OF PRENUPTIAL AGREEMENTS IN MIXED MARRIAGE - I Gusti Ayu Agung Siddhamahandari Surya Hadi Sugriwa; I Made Budi Arsika (Fakultas Hukum Universitas Padjadjaran, 2023)
The increasing intensity of mixed marriages involving Indonesian citizens and foreign citizens has given rise to legal problems related to joint property ownership. Marriage agreements have been seen as a solution to protect the legal rights of both parties. This article aims to analyze the implementation of the principle of freedom of contract in marriage agreements in mixed marriages and examine its legal consequences on the separation of immovable property, which was set as normative legal research using statutory, conceptual, and case approaches. The results suggest the principle of freedom of contract underlines that parties to a marriage agreement are free to make agreements regarding property or non-asset as long as they do not conflict with statutory regulations and legal order. However, marriage agreements should only regulate matters relating to assets because disputes on matters other than assets are relatively complex to determine the boundaries. The non-separation of immovable assets entails that Indonesian citizen partners may lose the opportunity to obtain rights over the immovable property because they will later become part of joint ownership with their foreign citizen partner. Therefore, separating assets would ensure Indonesian citizens' land rights.